2006
DOI: 10.1063/1.2361170
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nitrogen incorporation on the thermal stability of sputter deposited lanthanum aluminate dielectrics on Si (100)

Abstract: The thermal stability of sputter deposited LaAlOx and lanthanum aluminum oxynitride (LaAlON) dielectrics on top of Si (100) was evaluated after 1000°C rapid thermal annealing (RTA). A nitrogen concentration of ∼3at.% in the bulk LaAlON film was found to suppress crystallization as well as metal (lanthanum and aluminum) outdiffusion into the Si (100) substrate after the RTA treatment. These results suggest that film microstructure should be carefully controlled to inhibit impurity diffusion in the conventional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 24 publications
(18 reference statements)
0
3
0
Order By: Relevance
“…[14][15][16][17][18] Out-diffusion of La in amorphous and polycrystalline La-based high-k dielectrics have been studied by Sivasubramani and co-workers. No Hf or Ta was detected in the Si substrate after deprocessing (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…[14][15][16][17][18] Out-diffusion of La in amorphous and polycrystalline La-based high-k dielectrics have been studied by Sivasubramani and co-workers. No Hf or Ta was detected in the Si substrate after deprocessing (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown for amorphous LaAlO 3 films on Si that at a temperature of ~950 °C, the dielectric crystallizes, and significant amounts of La and Al diffuse into the Si. Only with significant nitridation (LaAlO x N y ) can the amorphous phase stability be improved, and La diffusion effectively be eliminated (23). We have demonstrated that for lanthanum silicate a nitridation anneal is unnecessary, as the amorphous phase is maintained after a 1000 °C, 10 sec N 2 RTA of ~1 nm EOT devices (13,24), as shown in the HRTEM image of Fig.…”
Section: Materials Properties Of Lanthanum Oxide and Silicate Thin Filmsmentioning
confidence: 93%
“…On an off-axis substrate, bombardment by all these species is decreased. [6][7][8][9] Oxide dielectric films can also be deposited by on-axis sputtering from a ceramic oxide target, [10][11][12] though anomalously high dielectric constants for well known materials such as Ta 2 O 5 have been attributed to quenched-in vacancies at high sputtering pressures. 3 Sputtering of dielectrics is an important research laboratory technique for the investigation of new candidate dielectric materials.…”
Section: Dielectric Response Of Tantalum Oxide Subject To Induced Ionmentioning
confidence: 99%